Masayang matuto mula sa Manobo the utilization of an interactive storybook about the importance and significance of the Agusan Manobo's culture and tradition to children, ages 8-10 - Ilano, Peter John O.
The Philippines is known to be rich in culture because of the diversity in the traditions, customs and beliefs of the different Philippine ethnolinguistic groups that set the foundation of Filipinos. These groups are important in the preservation of the Philippine culture for they hold histories and accountabilities in the image building of the country. One of them are the Manobo, one of the largest Philippine ethnolinguistic group.